A Regulatory Element in Intron 1 of the Cystic Fibrosis Transmembrane Conductance Regulator Gene - Smith, Annabel N.; Barth, Maria Luiza; McDowell, Tarra L.; Moulin, Danielle S.; Nuthall, Hugh N.; Hollingsworth, Michael A.; Harris, Ann (The Journal of biological chemistry, 1996)
The cystic fibrosis transmembrane conductance regulator (CFTR) gene exhibits a tightly regulated pattern of expression in human epithelial cells. The mechanism of this regulation is complex and is likely to involve a number of genetic elements that effect temporal and spatial expression. To date none of the elements that have been identified in the CFTR promoter regulate tissue-specific expression. We have identified a putative regulatory element within the first intron of the CFTR gene at 181+10kb. The region containing this element was first identified as a DNase I hypersensitive site that was present in cells that express the CFTR gene but absent from cells not transcribing CFTR. In vitro analysis of binding of proteins to this region of DNA sequence by gel mobility shift assays and DNase I footprinting revealed that some proteins that are only present in CFTR-expressing cells bound to specific elements, and other proteins that bound to adjacent elements were present in all epithelial cells irrespective of their CFTR expression status. When assayed in transient expression systems in a cell line expressing CFTR endogenously, this DNA sequence augmented reporter gene expression through activation of the CFTR promoter but had no effect in nonexpressing cells.